The synergistic effect of Er3+ and Ho3+ on temporal color tuning of upconversion emission in a glass host via a facile excitation modulation technique for anti-counterfeiting applications - Erol, Erdinc; Kibrisli, Orhan; Vahedigharehchopogh, Naji; Celikbilek Ersundu, Miray; Ersundu, Ali Ercin (ROYAL SOC CHEMISTRY, 2020)
Lanthanide-doped upconversion luminescent materials are highly promising for diverse applications, e.g., solid-state lighting, volumetric displays, and anti-counterfeiting, owing to their unique optical feature of color-tunable emission under near-infrared excitation. Hence, in this study, emission color tuning of Er3+/Ho3+ ions in a fixed glass host is investigated via a facile excitation modulation technique. The upconversion emission color from green to yellowish is tuned successfully by regulating the frequency of the irradiation source. The population and depopulation rates of related transitions are investigated through time-resolved photoluminescence and Judd-Ofelt analysis in order to elucidate the proposed mechanism of color tuning. Upconversion quantum yield values are measured in the range of 0.12 to 0.17% for a better comparison of the emission properties. Additionally, thermal, and structural properties are investigated to reveal the favorable properties of the selected tellurite glass host. Ultimately, several patterns are designed and constructed by a screen-printing technique using powdered glass to demonstrate its suitability as a multicolor imaging method for anti-counterfeiting applications. The temporal color tuning of upconversion emission via a facile excitation modulation technique in a glass host clearly indicates that the proposed Er3+/Ho3+ co-doped glasses can be potentially applied in the state-of-the-art technologies, especially for anticounterfeiting purposes.
Keywords: MU-M EMISSION; JUDD-OFELT PARAMETERS; ABSORPTION INTENSITIES; OPTICAL-ABSORPTION; ENERGY-TRANSFER; QUANTUM YIELD; NANOPARTICLES; EFFICIENT; SPECTRA; PHOTOLUMINESCENCE; Chemistry; Physics